Towards a commercial system for intraoperative manufacture of patient-specific guides for shoulder arthroplasty - Darwood,A; Hurst,S; Villatte,G; Fenton,R; Tatti,F; El-Daou,H; Reilly,P; Emery,R; Rodriguez,Y Baena F (EasyChair, 2019)
The accurate placement of orthopaedic implants according to a biomechanically derived preoperative plan is an important consideration in the long-term success of these interventions. Guidance technologies are widely described however, high cost, complex theatre integration, intraoperative inefficiency and functional limitations have prevented the widespread use. A novel, intraoperative mechatronics platform is presented, capable of the rapid, intraoperative manufacture of low-cost patient-specific guides. The device consists of a tableside robot with sterile drapes and some low cost, sterile disposable components. The robot comprises a 3D optical scanner, a three-axis sterile computer numerical control (CNC) drill and a two-axis receptacle into which the disposable consumables may be inserted. The sterile consumable comprises a region of rapidly setting moldable material and a clip allowing it to be reversibly attached to the tableside robot. In use, patient computed tomography (CT) imaging is obtained at any point prior to surgery and a surgical plan is created on associated software. This plan describes the axis and positioning of one or more guidewires which may, in turn, locate the prosthesis into position. Intraoperatively, osseous anatomy is exposed, and the sterile disposable is used to rapidly create a mould of the joint surface. Once set, the mould is inserted into the robot and an optical scan of the surface is taken followed by automatic surface registration, bringing the optical scan into the same coordinate frame of reference as the CT data and plan. The CNC drill is orientated such that the drill axis and position exactly matches the planned axis and position with respect to the moulded surface. A guide hole is drilled into the mould blank, which is removed from the robot and placed back into the patient with the moulded surface ensuring exact replacement. A wire is subsequently driven through the guide hole into the osseous anatomy in accordance with